คุณภาพชีวิตของประชาชนในพื้นที่อุตสาหกรรมแหลมฉบัง: Quality of Life in LaemChabang Industrial Area - มะลิ เกวลิน; เพียรประเสริฐ กนกพร (Journal of Applied Economics and Management Strategy, 2014)
การศึกษาคุณภาพชีวิตของคนในพื้นที่อุตสาหกรรมแหลมฉบังเป็นการวิจัยเชิงสำรวจ มีวัตถุประสงค์การศึกษา 2 ประการ ได้แก่ (1) เพื่อศึกษาลักษณะองค์ประกอบและระดับคุณภาพชีวิตของประชาชน และ (2) เพื่อวิเคราะห์อิทธิพลของปัจจัยที่มีต่อคุณภาพชีวิตของประชาชนพื้นที่ที่ทำการศึกษาได้แก่ชุมชนในเขตตำบลทุ่งสุขลา อำเภอศรีราชา จังหวัดชลบุรี ประกอบด้วยหมู่บ้านจำนวน 12 หมู่บ้านเป็นส่วนหนึ่งของเขตการปกครองของเทศบาลนครแหลมฉบัง และใช้กลุ่มตัวอย่างจำนวน 400 ตัวอย่าง การวิจัยนี้ได้ประยุกต์ใช้แนวคิดเกี่ยวกับการพัฒนา การพัฒนาชุมชน แนวคิดเกี่ยวกับการพัฒนาที่ยั่งยืน และแนวคิดเกี่ยวกับคุณภาพชีวิต ผลการศึกษา พบว่า คุณภาพชีวิตของประชาชนในเขตพื้นที่อุตสาหกรรมแหลมฉบังอยู่ในระดับปานกลางโดยพิจารณาจากเกณฑ์การชี้วัดที่ใช้ในการวิเคราะห์ระดับคุณภาพชีวิตของประชาชน ประกอบด้วยมาตรวัดคุณภาพชีวิตด้านความจำเป็นพื้นฐาน ด้านชีวิตความเป็นอยู่ ด้านโอกาสในการดำรงชีวิต และด้านความสะดวกสบาย เมื่อพิจารณารายละเอียด พบว่า ด้านความจำเป็นพื้นฐานมีคะแนนระดับคุณภาพชีวิตสูงที่สุด รองลงมาได้แก่ ด้านโอกาสในการดำรงชีวิต ด้านชีวิตความเป็นอยู่ และด้านความสะดวกสบายของชีวิต ตามลำดับ สำหรับปัจจัยที่มีอิทธิพลต่อระดับคุณภาพชีวิตของประชาชน ได้แก่ ปัจจัยส่วนบุคคล ประกอบด้วย เพศ อายุ สถานภาพครัวเรือน สถานภาพสมรส การศึกษา รายได้ การมีเงินออม การมีหนี้สิน การปล่อยกู้ และการครอบครองที่อยู่อาศัย ปัจจัยส่วนชุมชน ประกอบด้วย จำนวนสถาบันการศึกษาในชุมชน การมีสถานที่ออกกำลังกาย องค์กรในชุมชน ความสามารถในการปฏิบัติหน้าที่ของเจ้าหน้าที่ของรัฐในชุมชน This study examines the quality of life in Laem Chabang Industiral area. This study has used the survey research as a pilot method. The purposes of this survey are (1) to study the composition and quality of life of people who is living in Laem Chabang Industrial area. (2) to analyze the influential factors which affect the 12 communities or 12 villages. These communities are the parts of Laem Chabang Municipality in Tambon Thung Sukhla, Amphur Si Racha, Chonburi province as areas of study. The sample size consisted of 400 samples. The Community Development, Sustainable Development and Quality of life approach concepts have been applied to the study and used for analytical process. The result of this analysis indicates moderate level of quality of life of residents in Laem Chabang Industrial area. The various aspects such as the basic of life necessities (basic needs), the well-being as well as the social opportunities were used as the key indicators in measuring the quality of life of residents in this area of study in order to achieve the research findings. In addition, the findings are (1) the highest score level of the basic of life necessities (basic needs), (2) the social opportunity was secondary and the third was well-being respectively found in this research. The major influential factor which affects the quality of life of residents is personal factors; gender, age, social status, marital status, education, income, saving, debt, loan and housing tenure. Moreover, the community is another key factor which consists of the numbers of educational institutions in respective areas, the availability of local gymnasiums, local organizations and the capability and accessibility in performing duties of government representatives in the community